Localized immunotherapy via liposome-anchored anti-CD137 + IL-2 prevents lethal toxicity and elicits local and systemic anti-tumor immunity - Kwong, Brandon (2013)
Immunostimulatory agonists such as anti-CD137 and interleukin-2 (IL-2) have elicited potent anti-tumor immune responses in preclinical studies, but their clinical use is limited by inflammatory toxicities that result upon systemic administration. We hypothesized that by rigorously restricting the biodistribution of immunotherapeutic agents to a locally accessible lesion and draining lymph node(s), effective local and systemic anti-tumor immunity could be achieved in the absence of systemic toxicity. We anchored anti-CD137 and an engineered IL-2Fc fusion protein to the surfaces of PEGylated liposomes, whose physical size permitted dissemination in the tumor parenchyma and tumor-draining lymph nodes but blocked entry into the systemic circulation following intratumoral injection. In the B16F10 melanoma model, intratumoral liposome-coupled anti-CD137 + IL-2Fc therapy cured a majority of established primary tumors, while avoiding the lethal inflammatory toxicities caused by equivalent intratumoral doses of soluble immunotherapy. Immuno-liposome therapy induced protective anti-tumor memory and elicited systemic anti-tumor immunity that significantly inhibited the growth of simultaneously-established distal tumors. Tumor inhibition was CD8(+) T-cell-dependent and was associated with increased CD8(+) T-cell infiltration in both treated and distal tumors, enhanced activation of tumor-antigen-specific T-cells in draining lymph nodes, and a reduction in regulatory T-cells in treated tumors. These data suggest that local nanoparticle-anchored delivery of immuno-agonists represents a promising strategy to improve the therapeutic window and clinical applicability of highly potent but otherwise intolerable regimens of cancer immunotherapy.